Cultural interactions during the Zhou period (c. 1000-350 BC) : a study of networks from the Suizao corridor - Chen, Beichen, 1985- (Archaeopress archaeology., 2019)
This volume concerns the cultural interactions during the Zhou period of China (c. 1000-350 BCE) between the Suizao corridor (near the present-day Yangtze River region) and its contemporaries within or outside the Zhou realm. It mainly, but not exclusively, concentrates on bronze ritual vessels from the Suizao corridor.